ANALISIS TIPE BUDAYA POLITIK MASYARAKAT SUKU AKIT DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Lely Fitriana; Sri Erinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the many people of the Akit people who do not understand political problems, so that many parties are not responsible for abusing the situation. The formulation of the problem in this study is